Distal Evaluation of Functional performance with Intravascular sensors to assess the Narrowing Effect—combined pressure and Doppler FLOW velocity measurements (DEFINE-FLOW) trial: Rationale and trial design - Stegehuis, Valérie E.; Wijntjens, Gilbert W.M.; van de Hoef, Tim P.; Casadonte, Lorena; Kirkeeide, Richard L.; Siebes, Maria; Spaan, Jos A.E.; Gould, K. Lance; Johnson, Nils P.; Piek, Jan J. (The American heart journal, 2020)
It remains uncertain if invasive coronary physiology beyond fractional flow reserve (FFR) can refine lesion selection for revascularization or provide additional prognostic value. Coronary flow reserve (CFR) equals the ratio of hyperemic to baseline flow velocity and has a wealth of invasive and noninvasive data supporting its validity. Because of fundamental physiologic relationships, binary classification of FFR and CFR disagrees in approximately 30%-40% of cases. Optimal management of these discordant cases requires further study. The aim of the study was to determine the prognostic value of combined FFR and CFR measurements to predict the 24-month rate of major adverse cardiac events. Secondary end points include repeatability of FFR and CFR, angina burden, and the percentage of successful FFR/CFR measurements which will not be excluded by the core laboratory. This prospective, nonblinded, nonrandomized, and multicenter study enrolled 455 subjects from 12 sites in Europe and Japan. Patients underwent physiologic lesion assessment using the 0.014” Philips Volcano ComboWire XT that provides simultaneous pressure and Doppler velocity sensors. Intermediate coronary lesions received only medical treatment unless both FFR (≤0.8) and CFR (<2.0) were below thresholds. The primary outcome is a 24-month composite of death from any cause, myocardial infarction, and revascularization. The DEFINE-FLOW study will determine the prognostic value of invasive CFR assessment when measured simultaneously with FFR, with a special emphasis on discordant classifications. Our hypothesis is that lesions with an intact CFR ≥ 2.0 but reduced FFR ≤ 0.8 will have a 2-year outcome with medical treatment similar to lesions with FFR> 0.80 and CFR ≥ 2.0. Enrollment has been completed, and final follow-up will occur in November 2019.